Intramolecular carbolithiation of N-allyl-ynamides: an efficient entry to 1,4-dihydropyridines and pyridines – application to a formal synthesis of sarizotan - Gati, Wafa; Rammah, Mohamed M.; Rammah, Mohamed B.; Evano, Gwilherm (Beilstein Journal of Organic Chemistry, 2012)
We have developed a general synthesis of polysubstituted 1,4-dihydropyridines and pyridines based on a highly regioselective lithiation/6-endo-dig intramolecular carbolithiation from readily available N-allyl-ynamides. This reaction, which has been successfully applied to the formal synthesis of the anti-dyskinesia agent sarizotan, further extends the use of ynamides in organic synthesis and further demonstrates the synthetic efficiency of carbometallation reactions.
Keywords: carbolithiation; carbometallation; dihydropyridines; organolithium reagents; pyridines; sarizotan; ynamides

(untitled) - Ziegler, K.; Bähr, K. (Ber. Dtsch. Chem. Ges., 1928)

Organolithium: Selectivity for Synthesis - Clayden, J. (Elsevier, 2002)

Metal-Catalyzed Cross-Coupling Reactions - Marek, I.; Chinkov, N.; Banon-Tenne, D. (Carbometallation Reactions, 2004)

The Chemistry of Organolithium Compounds - Fañanás, F. J.; Sanz, R. (Wiley, 2006)

The Chemistry of Organocopper Compounds - Chemla, F.; Ferreira, F. (Wiley, 2009)

(untitled) - Basheer, A.; Marek, I. (Beilstein J. Org. Chem., 2010)

(untitled) - Coste, A.; Karthikeyan, G.; Couty, F.; Evano, G. (Angew. Chem., Int. Ed., 2009)

(untitled) - Jouvin, K.; Couty, F.; Evano, G. (Org. Lett., 2010)

(untitled) - Fadel, A.; Legrand, F.; Evano, G.; Rabasso, N. (Adv. Synth. Catal., 2011)

(untitled) - Jouvin, K.; Evano, G. (Chim. Oggi, 2011)

(untitled) - Laouiti, A.; Rammah, M. M.; Rammah, M. B.; Marrot, J.; Couty, F.; Evano, G. (Org. Lett., 2012)

(untitled) - Jouvin, K.; Heimburger, J.; Evano, G. (Chem. Sci., 2012)

(untitled) - Laouiti, A.; Jouvin, K.; Bourdreux, F.; Rammah, M. M.; Rammah, M. B.; Evano, G. (Synthesis, 2012)

(untitled) - Compain, G.; Jouvin, K.; Martin-Mingot, A.; Evano, G.; Marrot, J.; Thibaudeau, S. (Chem. Commun., 2012)

(untitled) - Jouvin, K.; Coste, A.; Bayle, A.; Legrand, F.; Karthikeyan, G.; Tadiparthi, K.; Evano, G. (Organometallics, 2012)

(untitled) - Evano, G.; Coste, A.; Jouvin, K. (Angew. Chem., Int. Ed., 2010)

(untitled) - DeKorver, K. A.; Li, H.; Lohse, A. G.; Hayashi, R.; Lu, Z.; Zhang, Y.; Hsung, R. P. (Chem. Rev., 2010)

(untitled) - Evano, G.; Jouvin, K.; Coste, A. (Synthesis, 2013)

(untitled) - Couty, S.; Liégault, B.; Meyer, C.; Cossy, J. (Org. Lett., 2004)

(untitled) - Couty, S.; Liegault, B.; Meyer, C.; Cossy, J. (Tetrahedron, 2006)

(untitled) - Couty, S.; Meyer, C.; Cossy, J. (Tetrahedron Lett., 2006)

(untitled) - Chechik-Lankin, H.; Livshin, S.; Marek, I. (Synlett, 2005)

(untitled) - Das, J. P.; Chechik, H.; Marek, I. (Nat. Chem., 2009)

(untitled) - Minko, Y.; Pasco, M.; Lercher, L.; Botoshansky, M.; Marek, I. (Nature, 2012)

(untitled) - Gourdet, B.; Lam, H. W. (J. Am. Chem. Soc., 2009)

(untitled) - Gourdet, B.; Rudkin, M. E.; Watts, C. A.; Lam, H. W. (J. Org. Chem., 2009)

(untitled) - Lavilla, R. (J. Chem. Soc., Perkin Trans. 1, 2002)

Targets in Heterocyclic Systems - Moreau, J.; Hurvois, J.-P.; Mbaye, M. D.; Renaud, J.-L. (Springer, 2009)

(untitled) - Bull, J. A.; Mousseau, J. J.; Pelletier, G.; Charette, A. B. (Chem. Rev., 2012)

(untitled) - Lukevitz, É. (Chem. Heterocycl. Compd., 1995)

Comprehensive Heterocyclic Chemistry II - Jones, G. (Pergamon, 1996)

(untitled) - Henry, G. D. (Tetrahedron, 2004)

Science of Synthesis: Houben-Weyl Methods of Molecular Transformations - Spitzner, D. (Thieme, 2004)

(untitled) - Park, Y. S.; Weisenburger, G. A.; Beak, P. (J. Am. Chem. Soc., 1997)

(untitled) - Curtis, M. D.; Beak, P. (J. Org. Chem., 1999)

(untitled) - Lim, S. H.; Curtis, M. D.; Beak, P. (Org. Lett., 2001)

(untitled) - Johnson, T. A.; Jang, D. O.; Slafer, B. W.; Curtis, M. D.; Beak, P. (J. Am. Chem. Soc., 2002)

(untitled) - Beak, P.; Lee, B. (J. Org. Chem., 1989)

(untitled) - Gilmore, K.; Alabugin, I. V. (Chem. Rev., 2011)

(untitled) - Gati, W.; Rammah, M. M.; Rammah, M. B.; Couty, F.; Evano, F. (J. Am. Chem. Soc., 2012)

(untitled) - Comins, D. L. (Tetrahedron Lett., 1983)

(untitled) - Zhang, Y.; Hsung, R. P.; Tracey, M. R.; Kurtz, K. C. M.; Vera, E. L. (Org. Lett., 2004)

(untitled) - Hamada, T.; Ye, X.; Stahl, S. S. (J. Am. Chem. Soc., 2008)

U.S. patent - Bottcher, H.; DeVant, R.; Greiner, H.; Bartoszyk, G.; Berthelon, J.-J.; Noblet, M.; Zeiller, J.-J.; Brunet, M. (Pyridyl chroman, 1998)

(untitled) - Bibbiani, F.; Oh, J. D.; Chase, T. N. (Neurology, 2001)

(untitled) - Rabiner, E. A.; Gunn, R. N.; Wilkins, M. R.; Sedman, E.; Grasby, P. M. (J. Psychopharmacol. (London, U. K.), 2002)

(untitled) - Bartoszyk, G.; Van Amsterdam, C.; Greiner, H.; Rautenberg, W.; Russ, H.; Seyfried, C. J. (Neural. Transm., 2004)

(untitled) - Olanow, C. W.; Damier, P.; Goetz, C. G.; Mueller, T.; Nutt, J.; Rascol, O.; Serbanescu, A.; Deckers, F.; Russ, H. (Clin. Neuropharmacol., 2004)

(untitled) - Bara-Jimenez, W.; Bibbiani, F.; Morris, M.; Dimitrova, T.; Sherzai, A.; Mouradian, M.; Chase, T. (Movement Disord., 2005)

(untitled) - Grégoire, L.; Samadi, P.; Graham, J.; Bédard, P.; Bartoszyk, G.; Di Paolo, T. (Parkinsonism Relat. Disord., 2009)

(untitled) - Gallemann, D.; Wimmer, E.; Hofer, C. C.; Freisleben, A.; Fluck, M.; Ladstetter, B.; Dolgos, H. (Drug Metab. Dispos., 2010)

(untitled) - Zhang, X. Q.; Egeland, M.; Svenningsson, P. (Psychopharmacology, 2011)

(untitled) - Gerlach, M.; Bartoszyk, G. D.; Riederer, P.; Dean, O.; van den Buuse, M. (J. Neural Transm., 2011)

Molecules under development at Newron Pharmaceuticals

(untitled) - Fadayi, O. O.; Senter, T. J.; Hahn, K. N.; Lindsley, C. W. (Chem.–Eur. J., 2012)

(untitled) - Couladourous, E. A.; Dakanali, M.; Demadis, K. D.; Vidali, V. P. (Org. Lett., 2009)